ANALISIS PRODUKSI TEMBAKAU RAJANGAN TIPE MUNTILANAN DALAM POLA KEMITRAAN CV. MERABU - PT. DJARUM KUDUS - Sumartono, Eko (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2016)
The aims of this research are to analyse the factors influenced production of tobacco and to count the tobacco productivity. This research applies a descriptive method and multiple regression analysis. Result of research indicates that level of input usage, production rate and level of productivity, quality of tobacco type Muntilanan has experienced a drastic degradation from the year 2005 to 2009. Hereinafter level of input usage experiences upsurge, although some inputs still experience a degradation. Number of partnership member, seed, NPK Fertil/Basal, Ortheen/Roteen 75 SP, Marcis, Hylan/ Suckericide Prime Plus, years of 2006, years of 2007, years of 2008 and years of 2009 are significant factors affecting production while number of partnership member,Seed, NPK Fertil/Basal, KNO3, Hylan/ Suckericide Prime Plus, Marcis, Year of 2006, and Year of 2009 are important factors to affect productivity.